Commissive Speech Acts of Sellers And Buyers in the Traditional Market of Rumah Tiga Village - Assel, Fauria; Lelapary, Happy Leunard (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The goal of this study is to characterize the commissive speech acts of merchants and customers at the traditional market of Rumah Tiga Village, Teluk Ambon. The method employed in this research is descriptive and qualitative. The research data refers to the words, phrases, and commissive speech acts of sellers and buyers, while the data sources are sellers and buyers consisting of two or more people who are currently involved in buying and selling transactions at the traditional market in Rumah Tiga Teluk Ambon. As for the data collection techniques utilized to gather data, they are observation and recording procedures. The observation technique was carried out by first reviewing the purchasing and selling interactions that occurred in the Rumah Tiga traditional market, while the recording technique was done by recording all the utterances and activities of traders and purchasers during the buying and selling process. The results of this study indicated that the commissive speech acts that regularly occur in transactions between vendors and purchasers at the traditional market in Rumah Tiga are promising, swearing, intending, offering, and vowing.